Measuring urban sprawl on geospatial indices characterized by leap frog development using remote sensing and GIS techniques - Hj. Mohd. Noor, Norzailawati; Asmawi, M. Zainora; Rusni, Nuraulia (IOP Publishing Ltd, 2014)
Characterizing urban sprawl using spatial measures requires a concise definition of what constitutes sprawling urban spatial patterns. This research attempts to study a measurement of defining sprawl by using leapfrog development index through remote sensing and GIS approach. The IKONOS pan-sharpened and SPOT-5 with 1 and 2.5 meter resolution were used and combined with Geographical information system (GIS) database to analyze the geospatial indicators using the leapfrog development index. Kuantan city has been selected as a study area to examine the leapfrog development based on land use pattern for year 2012. The findings show Kuantan has identified as non-sprawling cities with result from characterization in leapfrog development that has been tested. However, the gap between sprawl and nonsprawling was very low. It is anticipated this research will provide a new direction in sprawl nationally that address finding of sprawl at the atomic level and present a robust analytical approach for characterizing urban development in city scale at once promoting a city via GIS & Remote Sensing technology respectively towards Digital and Green cities.